The Mandatory ID Card Population Through Digital Identity Activation (IKD) - Melati, Dhea Ananda; Maulidina, Puspita; Wulandari, Sri (Jurnal Polisci, 2025)
Background. Digital Population Identity (IKD) is an officially designed identity that utilizes technology to facilitate the public in obtaining various important documents such as e-KTP or Family Cards. Data extracted from the Population Administration Data Processing (PDAK) shows that Sememi Subdistrict has the highest number of IKD activation targets with a total of 31,195 residents and those who already have IKD with a total of 5,228 residents. Aims. The purpose of the IKD is to understand the activation process, supporting factors, obstacles, and efforts involved. Methods. The method used is qualitative, while the theory employed is from Lijan Poltak Sinambela (2019). Result. The research results show that the Sub-district has assigned all staff to provide services at each Neighborhood unit community hall. Conclusion. The Sub-district provides evening services every Tuesday and Wednesday, and staff conduct outreach services to ensure that residents have equal access to public services in Sememi Sub-district. Implementation. To implement IKD activation services, it is necessary to conduct more socialization, provide guidelines that are easy for residents to understand, and actively carry out outreach services.